Pengaruh Pembelajaran Kewirausahaan dan Motivasi Wirausaha Terhadap Niat Berwirausaha - Ismayanti, Dea Try; Affriliani, Affriliani; Dinda Intan Hasanah, Dinda Intan Hasanah; Nanita Laudry, Nanita Laudry; Muhammad Zulpikar, Muhammad Zulpikar; Pandhu Qistiawan, Pandhu Qistiawan (Indonesian Educational Administration and Leadership Journal (IDEAL), 2021)
The purpose of this study was to describe the Effect of Entrepreneurship motivation and learning on the Entrepreneurial Intentions of Students of the Faculty of Teaching and Education, University of Jambi. The research method used is theoretical review or literature review. The results suggest that the concepts and theories of policy experts, especially regarding the formulation of public policies, can be used for all fields of policy science. Several studies and theories regarding the formulation of an Influence of Entrepreneurship Learning and Entrepreneurial Motivation on Entrepreneurial Intentions of Students of the Faculty of Education and Science, Jambi University. Several studies and theories regarding policy formulation can overcome all policy problems faced by institutions and institutions of the Faculty of Teaching and Education, University of Jambi.